A neutron study of sealed pottery from the grave-goods of Kha and Merit. Issue 7 (5th June 2017) - Andreani, C.; Aliotta, F.; Arcidiacono, L.; Borla, M.; Di Martino, D.; Facchetti, F.; Ferraris, E.; Festa, G.; Gorini, G.; Kockelmann, W.; Kelleher, J.; Malfitana, D.; et al.
Abstract : This work presents the first neutron characterization of artefacts from the grave-goods of Kha and Merit, a unique cultural treasure of mankind and preserved at the Museo Egizio in Turin. Abstract : This work presents the first neutron characterization of artefacts from the grave-goods of Kha and Merit, a unique cultural treasure of mankind and preserved at the Museo Egizio in Turin. This magnificent collection, discovered in the early years of the last century, includes an impressive amount of artefacts such as coffins, textiles, metallic and ceramic pottery, and alabaster containers. The present study investigates two sealed potteries, using enhanced Neutron Tomography, Radiography, and Prompt Gamma Activation Analysis techniques. The neutron probe provides access to the morphological reconstructions of the inner parts of the vases and to map, with unprecedented details, the elemental composition of the surfaces and bulk areas of the potteries. The present work extends the knowledge to hitherto unknown contents of the sealed vases unlocking their secrets.